On-field rehabilitation in football: current practice and perceptions. A survey of the English Premier League and Football League - Armitage, M.; McErlain-Naylor, S. A.; Devereux, G.; Beato, M.; Iga, J.; McRobert, A.; Roberts, S.; Buckthorpe, M. (Science and Medicine in Football, 2025)
Introduction: Return to play related research is increasing rapidly, with two recent competency-based frameworks offering conceptualised support for on-field rehabilitation (OFR) decision-making. It is still unknown, however, who is responsible for OFR and how they typically select, monitor, and progress OFR processes. Aims: The purpose of this study was to investigate current OFR practice within English professional football to support practitioners with decision-making and highlight opportunities for future research related to the design, monitoring, and progression of OFR. Methods: Sixty-nine practitioners responsible for the design and implementation of OFR at 69 clubs (75% of the English Premier League and Football League) responded to a survey containing 30 questions (14 open and 16 closed). Results: The main findings were that therapists (physiotherapists/sports therapists) have the largest influence on OFR, followed by physical performance coaches (sports scientists/strength and conditioning coaches), technical coaches and medical doctors. There was more agreement for the ordering of specific OFR drills earlier in the process when activities are easier to control. The most frequently reported objective monitoring tool was global positioning systems (GPS), with functional/clinical experience/expertise remaining subjectively vital. GPS outputs (e.g., sprint metrics and accelerations/decelerations) were most used for between session decision-making, with verbal communication being key for within session decision-making. Conclusion: Future research should use evidence of current practice, such as drill design and monitoring techniques, to explore drill-level analysis and give practitioners greater insights into which stage of current OFR frameworks specific drills fall, and how they might be more objectively progressed/regressed.